Multifunctionality applied to furniture design for small spaces (Estudos em Design, 2015)
The multifunctionality is one of the many terms used in industrial design, particularly with regard to the furniture design for small spaces. This and other related terms are frequently used to describe characteristics of the furniture in question. Through a bibliographic research in the area of design and others related, the terms and their respective definitions found in each publication are presented. The research reveals a lack of definitions of the terms in publications in the studied field, as well as its misapplication, often confusing them. The study aims to elucidate the terms raised by proposing definitions for each of them, especially the multifunctionality. Thereby we seek to distinguish them and avoid applying these in error.
Keywords: Multifunctionality; Design; Use of space